#TITLE_ALTERNATIVE# - ABDUL AZIZ (NIM 15106053); Pembimbing: Dr. rer. nat. Poerbandono, UMAR
The purpose of this study is to map the sediment dynamics between two different epochs. The map will be related with the wind climate at the study area. The study area is located on the Pramuka Island, Karya Island, and Semak Daun Island. Sediment properties data used are sediment properties data in July 2008 and March 2010. Wind data was downloaded from NOAAÃ‚Â’s site from 1948 to 2009. The sediment map is made based on the properties of sediment samples. The sediment properties in March 2010 are compared to the sediment properties in July 2008 to obtain sediment dynamics. Wind data were processed in order to get monthly wind characteristics and wind climate in the study area. The sediment dynamics were then connected to the wind characteristics to see the influence of wind climate towards the sediment dynamics. Based on the study, it shows that the energy in the north of the Pramuka Island is greater than in the south, while the energy in the east of Karya Island is greater than in the west. Tiny sediments that are contained at the first epoch on Semak Daun Island are not occured at the second epoch. The east monsoon blows from the south-east, whereas the west monsoon blows from the north-west. The west monsoon has a higher speed than the east monsoon. The east monsoon affects the sediment transport on the Semak Daun Island at the first epoch, so that the energy of sediment transfer blows from south-east. The west monsoon affects the sediment transport on the Semak Daun Island at second epoch, so the energy of sediment transfer blows from north-west.